Pancreatic Metastases from Renal Cell Carcinoma. Postoperative Outcome after Surgical Treatment in a Spanish Multicenter Study (PANMEKID) - Blanco-Fernández, Gerardo; Fondevila-Campo, Constantino; Sanjuanbenito, Alfonso; Fabregat-Prous, Joan; Secanella-Medayo, Luís; Rotellar-Sastre, Fernando; Pardo-Sánchez, Fernando; Prieto-Calvo, Mikel; Marín-Ortega, Hector; Sánchez-Cabús, Santiago; Diez-Valladares, Luís; Alonso-Casado, Oscar; et al. (Elselvier, 2022)
Background: Renal Cell Carcinoma (RCC) occasionally spreads to the pancreas. The purpose of our study is to evaluate the short and long-term results of a multicenter series in order to determine the effect of surgical treatment on the prognosis of these patients. Methods: Multicenter retrospective study of patients undergoing surgery for RCC pancreatic metastases, from January 2010 to May 2020. Variables related to the primary tumor, demographics, clinical characteristics of metastasis, location in the pancreas, type of pancreatic resection performed and data on short and long-term evolution after pancreatic resection were collected. Results: The study included 116 patients. The mean time between nephrectomy and pancreatic metastases' resection was 87.35 months (ICR: 1.51-332.55). Distal pancreatectomy was the most performed technique employed (50 %). Postoperative morbidity was observed in 60.9 % of cases (Clavien-Dindo greater than IIIa in 14 %). The median follow-up time was 43 months (13-78). Overall survival (OS) rates at 1, 3, and 5 years were 96 %, 88 %, and 83 %, respectively. The disease-free survival (DFS) rate at 1, 3, and 5 years was 73 %, 49 %, and 35 %, respectively. Significant prognostic factors of relapse were a disease free interval of less than 10 years (2.05 [1.13-3.72], p 0.02) and a history of previous extrapancreatic metastasis (2.44 [1.22-4.86], p 0.01). Conclusions: Pancreatic resection if metastatic RCC is found in the pancreas is warranted to achieve higher overall survival and disease-free survival, even if extrapancreatic metastases were previously removed. The existence of intrapancreatic multifocal compromise does not always warrant the performance of a total pancreatectomy in order to improve survival
Keywords: Riñones - Cáncer; Cirugía; Cáncer - Recidiva; Metástasis; Metastases; Pancreatectomy; Recurrence; Renal cell carcinoma